Redescription of Melanagromyza sojae (Zehntner) from India and Nepal - Thapa, Ram Bahadur (Nepalese Journal of Biosciences, 2013)
Six new species of other stem flies infesting mostly legumes were also discovered under the genus Melanagromyza (stem flies) from Pantnagar, Northern India. These were: M. species new ex stems of Cassia sp. (proposed name M. pathaki new species); M. species new ex stems of Glycine max (Linn.) Merril. (proposed name M. glycini new species); M. species new ex stems of Medicago denticulata willd. (proposed name M. denticulata Willd. new species); M. species new ex stems of Pisum sativum Linn. (proposed name M. pisiphaga new species); M. species new ex stems of Trifolium pratense Linn,. (proposed name M. sehgali new species) and M. species new ex stems of Vicia faba Linn. (proposed name M. vicivora new species). New names have been proposed to them as per International rules of Zoological Nomenclature. Other stem flies redescribed by author include: Ophiomyia centrosematis de Meijere, Opmiormyia phaseoli (Tryon) and Ophiomyia cicerivora. More than one thousand male genitalia slides were prepared for this study. Variations in morphology and genitalia characters have been described between and within the species. Melanagromyza sojae (Zehtner) has been redescribed here. DOI: http://dx.doi.org/10.3126/njbs.v2i0.7491 Nepalese Journal of Biosciences 2 : 64-70 (2012)